The Influence of the Contextual Teaching and Learning Model on the Reconstruction of National Law in the Perspective of the Philosophy of Pancasila - Gulyanto, Bambang; Vera, Susanti Sansi; Sari, Fany Duma; Azimah, Wan; Agustini, Sri Rahayu (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
Indonesia's national legal system faces challenges in realizing substantive justice in accordance with the values of Pancasila. Many legal products are formalistic and technocratic, often detached from the nation's ethical, spiritual, and social roots. In this context, the reconstruction of national law is a necessity, namely restructuring the legal system to align with the noble values of Pancasila. This reconstruction is not only normative-institutional but also demands transformation at the level of legal education. The Contextual Teaching and Learning (CTL) learning model offers an innovative approach that connects legal theory with the social context and values of Pancasila. This research uses qualitative methods with a case study at a state law faculty. Data were obtained through interviews, observations, and curriculum documentation. The findings indicate that CTL is able to increase students' legal awareness, foster ethical understanding, and encourage critical engagement with existing legal products. Students who learn through the CTL approach demonstrate the ability to assess law not only from a legal perspective, but also from the perspective of substantive justice and human values. They are more active in discussions, reflective in their thinking, and courageous in criticizing laws deemed inconsistent with the principles of Pancasila. Furthermore, CTL has been shown to internalize values such as deliberation, honesty, and responsibility in the character of law students. However, the implementation of CTL faces several challenges, such as limited lecturer training and a lack of contextual curriculum integration. Therefore, for CTL to function optimally as a bridge between legal education and national legal reconstruction, institutional support and ongoing pedagogical strengthening are needed. Thus, CTL has great potential as a transformative strategy in shaping an Indonesian legal system that is just, responsive, and Pancasila-based.